The Enhancing Single Cell Protein Production of Saccharomyces cerevisiae Using Soybean Hull Waste with Dextrose Variations - ., Musa'adah; Darniwa, Adisty Virakawugi; Kartika Sari, Dede (Universitas Muhammadiyah Surakarta, 2025)
Single Cell Protein (SCP) is a microprotein derived from the dry biomass of non-pathogenic microorganisms and offers a promising alternative protein source for both humans and animals. One of the advantages of SCP production is its potential to utilize organic waste as a growth medium, thereby contributing to environmental sustainability. Soybean hull waste has been identified as a nutrient-rich substrate capable of supporting the growth of various microorganisms used in SCP production. This study aimed to optimize the growth medium for S. cerevisiae by utilizing soybean hull waste supplemented with varying concentrations of dextrose, in order to determine the most effective dextrose level for SCP production. The experiment involved cultivating S. cerevisiae in filtrates of soybean hull waste supplemented with five different dextrose concentrations: 0% (FD0), 1% (FD1), 2% (FD2), 3% (FD3), and 4% (FD4), as well as a standard Yeast Potato Dextrose (YPD) medium used as a control. Fermentation was initiated with an inoculum concentration of 1.3×10⁶ CFU/mL across all treatments then incubated at 28–30°C for 72 hours. Biomass, moisture content and protein content of yield were measured at the end of the fermentation. The results showed the dextrose conc. significantly affected pH levels, biomass yield, moisture, and protein content of the final product. Higher dextrose conc. generally led to better yield. Among the treatments, FD4 (4% dextrose) produced the highest biomass (0.091 g/10 mL) and protein content (18.43%). These finding showed that soybean hull waste can serve as a sustainable growth medium for the S. cerevisiae-SCP production, with 4% dextrose supplementation yielding the most optimal results.